Clinical predictive factors for diagnosis of MOG-IgG and AQP4-IgG related paediatric optic neuritis: a Chinese cohort study. Issue 2 (16th November 2020) - Yang, Mo; Wu, Yiqun; Lai, Mengying; Song, Honglu; Li, Hongen; Sun, Mingming; Xie, Lindan; Zhou, Huanfen; Xu, Quangang; Wei, Shihui; Wu, Weiping
Abstract : Background: Different glial-autoantibodies-related paediatric optic neuritis (ON) are associated with different clinical characteristics and prognosis that require different treatments. Because glial autoantibody detection is not available in some parts of the world and there is often a delay in obtaining results, clinical factors that can be used to predict the subtype of paediatric ON are needed. Methods: This was a single-centre retrospective cohort study. Children who presented with their first ON attack and with complete clinical data were included in the analysis. Single and multiple parameters for predicting paediatric myelin oligodendrocyte glycoprotein immunoglobin-associated ON (MOG-ON) and aquaporin-4 immunoglobin-related ON (AQP4-ON) were calculated. Results: 78 paediatric patients had their first ON attack from January 2016 to December 2019, of whom 69 were included in the final analysis, including 33 MOG-ON cases, 17 AQP4-ON cases and 19 Seronegative-ON cases. For predicting paediatric MOG-ON, the most sensitive predictors were 'male or optic disc swelling (ODS) or bilateral' (sensitivity 0.97 (95% CI 0.82 to 1.00)) and 'follow-up visual acuity (VA) ≤0.1 logMAR or ODS' (sensitivity 0.97 (95% CI 0.82 to 1.00)), and the most specific factor was 'Age ≤11 y and simultaneous CNS involvement' (specificity 0.97 (95% CI 0.84 to 1.00)). For predicting paediatric AQP4-ON, the most sensitive predictor was 'Female or without ODS' (sensitivity 1.00 (95% CI 0.77 to 1.00)), and the most specific factors were Neurological history (sensitivity 0.94 (95% CI 0.83 to 0.98)) and follow-up VA >1.0 logMAR (sensitivity 0.96 (95% CI 0.86 to 0.99)). Conclusion: According to our data from a Chinese paediatric cohort, using multiple parameters increases the sensitivity and specificity of diagnosing paediatric MOG-ON and AQP4-ON. These can assist clinicians in diagnosing and treating paediatric ON when glial autoantibody status is not available.